Household costs incurred when seeking and receiving paediatric tuberculosis services: a survey in Cameroon and Kenya - Nyashadzaishe Mafirakureva; Sushant Mukherjee; Lise Denoeud-Ndam; Rose Otieno-Masaba; Boris Tchounga; Millicent Anyango Ouma; Stephen Siamba; Saint-Just Petnga; Patrice Tchendjou; Martina Casenghi; Appolinaire Tiam; Peter J Dodd (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Elimination of catastrophic costs due to tuberculosis (TB) is one of the three targets of the World Health Organization (WHO) End TB Strategy. Limited data have yet been reported on the costs experienced by households of children receiving TB services. We quantified the economic impact on households with children seeking and receiving TB services during the Catalyzing Pediatric TB Innovations (CaP-TB) project in Cameroon and Kenya. # Methods Within the INPUT stepped-wedge cluster-randomised study evaluating the effect of CaP-TB integration of TB services in paediatric entry points, we designed a cross-sectional facility-based survey with retrospective data collection using a standardised questionnaire adapted from the WHO Global taskforce on TB patient cost generic survey instrument. Caregivers of children receiving TB services (screening, diagnosis and treatment of drug-sensitive TB) during the CaP-TB project were interviewed between November 2020 and June 2021. Direct medical, direct non-medical, and indirect costs for TB services were analysed following WHO Global taskforce recommendations. We used the human capital and output-based approaches to estimating income loss. All costs are presented in 2021 US dollars. # Results A total of 56 caregivers representing their households (Cameroon, 26, and Kenya, 30) were interviewed. The median household costs for TB services, estimated using the human capital approach, were \$255 (IQR; \$130-631) in Cameroon and \$120 (\$65-236) in Kenya. The main cost drivers across both countries were direct non-medical costs (transportation and food), 52%; and medical costs, 34%. Approximately 50% of households reported experiencing dissavings (taking a loan, or selling an asset) to deal with costs related to TB disease. Using a threshold of 20% of annual household income, 50% (95%CI; 37-63%) of households experienced catastrophic costs when using the human capital approach; (46% (95%CI; 29-65%) in Cameroon and 53% (95%CI; 36-70%) in Kenya). Estimated costs and incidence of catastrophic costs increased when using the output-based approach in a sensitivity analysis. # Conclusions Accessing and receiving TB services for children results in high levels of cost to households, despite the provision of free TB services. Strategies to reduce costs for TB services for children need to address social protection measures or explore decentralisation. **Registration:** https://clinicaltrials.gov/ct2/show/NCT03862261.